Development Of An Arduino Iot System Solar Cell Electronic Practicum Guide Based On An Automatic Feed Thrower Prototype To Develop Students' Science Process Skills - Wardana, Rendy Wikrama; Anggraini, Yestilia; Firdaus, M. Lutfi; Yanti, Fitri April; Wibowo, Firmanul Catur; Fitri, Elsi Adelia (STKIP Singkawang, 2025)
Science learning, especially in physics, is an abstract concept and difficult for students to understand. In addition, there is also a need for a bridge that can connect physics concepts with life in the student's daily environment. Therefore, technological innovations are needed in learning such as developing an electronic practicum guidebook for solar cells, Arduino IoT systems based on automatic feed thrower prototypes to develop students' science process skills. This study used a 4D model. The subjects of this study were 6th semester S1 Science students totaling 52 students. The data generation instrument uses questionnaires and implementation observation sheets. Data analysis techniques use qualitative and qualitative. Based on the results of the validation that has been carried out, the practicum guide that has been prepared as a whole has eligibility criteria that are very feasible to use, with a percentage of 92.25%, while the students' science process skills in the solar cell electronic practicum guide for the Arduino IoT system based on the prototype of this automatic feed thrower get an average of 92% with a very good category so that it can be considered that students are good at understanding and Work on the basis of practicum guidelines developed.